Rancang Bangun Sistem Informasi Berobat Jalan di Klinik Cikijing Rancaekek - Sifa Ramdini; Encep Supriatna; Usup Supendi (INTERNAL (Information System Journal), 2022)
Information technology provides benefits for human life. Utilization of technology in the service sector is needed because it can provide optimal service to clients. Meanwhile, currently the outpatient data processing at the Cikijing Rancaekek Clinic is still manual, causing several obstacles, namely difficulty in finding patient data because they are still looking through medical record cards, difficulty in making reports quickly and accurately and difficulty in calculating treatment costs.The purpose of this study is to make it easier to find patient data, make reports quickly, and make the calculation of patient treatment costs more effective. The method used is SDLC with a waterfall model and data collection techniques. System analysis and design tools used for this final project are Flow Map, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), Data Dictionary (Data Dictionary), and Structure Chart. For program implementation using Microsoft Visual Foxpro9.0 programming language. In this system, it is concluded to overcome the problems that have occurred in the old system, so that it can assist in the process of searching for patient data, making reports and calculating treatment costs.